Fast gene transfer into the adult zebrafish brain by herpes simplex virus 1 (HSV-1) and electroporation: methods and optogenetic applications - Zou, Ming; De Koninck, Paul; Neve, Rachael L.; Friedrich, Rainer W. (Frontiers in Neural Circuits, 2014)
The zebrafish has various advantages as a model organism to analyze the structure and function of neural circuits but efficient viruses or other tools for fast gene transfer are lacking. We show that transgenes can be introduced directly into the adult zebrafish brain by herpes simplex type I viruses (HSV-1) or electroporation. We developed a new procedure to target electroporation to defined brain areas and identified promoters that produced strong long-term expression. The fast workflow of electroporation was exploited to express multiple channelrhodopsin-2 variants and genetically encoded calcium indicators in telencephalic neurons for measurements of neuronal activity and synaptic connectivity. The results demonstrate that HSV-1 and targeted electroporation are efficient tools for gene delivery into the zebrafish brain, similar to adeno-associated viruses and lentiviruses in other species. These methods fill an important gap in the spectrum of molecular tools for zebrafish and are likely to have a wide range of applications.